The research work as a way to improve the readiness of prospective teachers to organize extra-curricular educational activities for younger students (Pedagogy of Higher and Secondary Education, 2012)
Titun O. The research work as a way to improve the readiness of prospective teachers to organize extra-curricular educational activities for younger students.The article deals with the problem of peculiarities of research work of would-be teachers of primary school. The research work is considered to be one of the main factors of improvement of readiness to do extraclass activities with primary school pupils.
Keywords: research work; would-be teachers of primary school; extraclass activities; primary school pupils